Aging-related episodic-like memory decline in dogs - Sanches, Felipe Jacques [UNESP]; de Melo, Jéssica Cardia [UNESP]; Ferreira, Sabrina Palha [UNESP]; Trinca, Luzia Aparecida [UNESP]; Arambula, Omar Gurrola [UNESP]; Padovani, Flavia Helena Pereira [UNESP]; Schelp, Arthur Oscar [UNESP]; Amorim, Rogério Martins [UNESP] (Elsevier, 2022)
Episodic memory, in humans, is the memory most affected by age-related deterioration or the constitution of neurodegenerative pathologies, such as Alzheimer's disease. However, it is unknown whether this relationship is also present in nonhuman animals. Since studies in birds, rats, primates, and dogs have been shown to have episodic-like memory, more studies aiming to improve the present understanding of this relationship in nonhuman animals are important to aid the development of new translational models for neurodegenerative disorders. Knowing that dogs (Canis familiaris) represent a promising experimental model for neurodegenerative disorders, a memory retrieval test was conducted with 90 clinically healthy domestic dogs of different ages, both sexes, and distinct breeds, for the purpose of evaluating episodic-like memory. The present study adapted a test that corroborates episodic memory requirements through incidental codification of experienced events. We performed a test with two exposure phases, with different characteristics between them, so that in the third phase it was necessary to integrate previous experiences in order to achieve success in the test. In our study, it was possible to verify the decline of episodic memory in elderly dogs, even clinically healthy, regardless of the dogs’ sex and size. This episodic-like memory decline observed in elderly dogs may be related to the physiological process of aging or preclinical pathological manifestation of cognitive impairment, similar as reported in humans. More studies should be carried out evaluating episodic-like memory in dogs with suspected of canine cognitive dysfunction syndrome in order to better understand the physiological and pathological behavior of this type of memory in canine species.
Keywords: Cognitive deficit; Cognitive test; Dementia; Incidental memory